In Situ Quantitative Measurement of Rare Earth Elements in Uranium Oxides by Laser Ablation‐Inductively Coupled Plasma‐Mass Spectrometry. Issue 3 (14th February 2013) - Lach, Philippe; Mercadier, Julien; Dubessy, Jean; Boiron, Marie‐Christine; Cuney, Michel
Abstract : Advances in the quantification of rare earth elements (REE) at the micrometric scale in uranium oxides by laser ablation‐inductively coupled plasma‐mass spectrometry are described. The determination of the best analytical conditions was tested using a uranium oxide (Mistamisk) the concentrations of REE in which were previously estimated by other techniques. Comparison between the use of U or Pb as an internal standard clearly showed a diameter‐dependent fractionation effect related to Pb at small crater diameters (16 and 24 μm), which was not found for U. The quantification of REE contents in uranium oxide samples using both matrix‐matched (uranium oxide) and non‐matrix‐matched (NIST SRM 610 certified glass) external calibrators displayed no significant difference, demonstrating a limited matrix effect for REE determination by LA‐ICP‐MS. Moreover, no major interferences on REEs were detected. The proposed methodology (NIST SRM 610 as external calibrator and U as internal standard) was applied to samples from uranium deposits from around the world. The results showed that LA‐ICP‐MS is a suitable analytical technique to determine REE down to the μg g −1 level in uranium oxides at the micrometre scale and that this technique can provide significant insights into uranium metallogeny.